Pemetaan Indikasi Jasa Ekosistem Daerah Aliran Sungai Masupu - MF Mappiasse; M Sahid; Muliana Dj (Program Studi Kehutanan Universitas Muslim Maros, 2019)
This study aims to identify and mapping the indication of ecosystem services in Watershed Masupu. The usefulness of this research as one of the reference in the determination of status of support capacity of environmental capacity in the preparation of environmental management and control plan, spatial plan of region, and become reference for next researcher. Masupu Watershed is upperstream part of Saddang Watershed which is administratively located in some areas of Mamasa Regency, Mamuju Regency, Pinrang Regency, Tana Toraja Regency and North Toraja Regency. This research uses the method of expert judgement of geomorphology and landcover to ecosystem services, which then analyzed of pairwise comparison matrix and data processing is done with the help of geographic information system. The results of this study indicate that the geomorphology of the Masupu Watershed is 8 types and landcover of the Masupu Watershed area is 12 types. The main function of the Masupu Watershed ecosystem services in the upperstream is the ecosystem services of recreation and ecotourism. The main function in the middle of Masupu Watershed is the clean water ecosystem services.